Formulation And Evaluation Of Effervescent Garnules Using Lemon Leaves And Ajwain Extact - Mr. Rahul S. Mohan; Ms. Shweta R. Agrawal; Ms. Neha B. Gaikwad; Ms. Arti P. Jadhav; Ms. Divya K. Vaykos (Revista Electronica de Veterinaria, 2024)
The main purpose of this research was to formulate and evaluate the effervescent granules of lemon leaves and ajwain extract by wet granulation method. According to the observations of this research, the effervescent granules overcomes the 5 benefits than the regular liquid dosage form like pleasant taste compared to regular tablets, distributed more evenly, increased liquid intake, easy alternative to regular tablets, easy alternative to regular tablets as well as it increases the absorption, stability, quicker and prolong the onset of action with antioxidant and antacid activity.       As per the formulated evaluation were different parameters like bulk density (0.52), tapped density (0.68), angle of repose (30.5), carr’s index (23.5), hausner’s ratio (1.30), effervescence time (30-50 sec), its  shows green in colour, characteristics in  odour and amorphous granular appearance.